The influence of` preseason training phase and training load on body composition and its relationship with physical qualities in professional junior rugby league players - Dobbin, N.; Gardner, A.; Daniels, M.; Twist, C. (Journal of Sports Sciences, 2018)
This study investigated changes in body composition in relation to training load determined using RPE and duration (sRPE), and its relationship with physical qualities over a preseason period. Sixteen professional academy players (age = 17.2 ± 0.7 years; stature = 179.9 ± 4.9 cm; body mass = 88.5 ± 10.1 kg) participated in the study. Body composition was assessed before and after each training phase and physical qualities assessed at the start and end of preseason. Across the whole preseason period, skinfold thickness, body fat percentage and fat mass were most likely lower (ES = -0.73 to -1.00), and fat free mass and lean mass were likely to most likely higher (ES = 0.31 to 0.40). Results indicated that the magnitude of change appeared phase-dependent (ES = -0.05 to -0.85) and demonstrated large individual variability. Changes in physical qualities ranged from unclear to most likely (ES = -0.50 to 0.64). Small to moderate correlations were observed between changes in body composition, and TL with changes in physical qualities. This study suggests training phase and TL can influence a player`s body composition; that large inter-participant variability exists; and that body composition and TL are related to the change in physical qualities.